1840 R.I. Pub. Laws 3, 17, An Act to Regulate the Militia, § 46 - (:unkn) unknown (General Publisher, 1840)
If any non-commissioned officer or private shall become a pauper, vagabond, or common drunkard, or be convicted of any infamous crime, he shall be forthwith disenrolled from the militia.”
--
Keywords: ARMED FORCES